1987
DOI: 10.1073/pnas.84.16.5625
|View full text |Cite
|
Sign up to set email alerts
|

The G glycoprotein of human respiratory syncytial viruses of subgroups A and B: extensive sequence divergence between antigenically related proteins.

Abstract: Two major antigenic subgroups (designated A and B) have been described for human respiratory syncytial virus (RSV). Previously, on the basis of reactivity patterns with monoclonal antibodies, the greatest intersubgroup variation was shown to occur in the G protein, the putative attachment glycoprotein. To delineate the molecular basis for this variation, we have determined the nucleotide and deduced amino acid sequences of the G mRNAs and proteins representing a subgroup A (Long strain) and a subgroup B (18537… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
470
0
30

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 457 publications
(526 citation statements)
references
References 25 publications
18
470
0
30
Order By: Relevance
“…1. Amino acid sequences encompassing residues 149-197 of the G proteins of A (Satake et al, 1985;Wertz et al, 1985) and B (Johnson et a]., 1987;Sullender et al, 1990 subtypes of human RSV, bovine RSV (Lerch et al, 1990), and ovine RSV (Alansari & Potgeiter, 1993).…”
Section: Ssqksn-seiqqdysdfqilpy---n--egdsa-lsl-qdrsesild-amentioning
confidence: 99%
See 2 more Smart Citations
“…1. Amino acid sequences encompassing residues 149-197 of the G proteins of A (Satake et al, 1985;Wertz et al, 1985) and B (Johnson et a]., 1987;Sullender et al, 1990 subtypes of human RSV, bovine RSV (Lerch et al, 1990), and ovine RSV (Alansari & Potgeiter, 1993).…”
Section: Ssqksn-seiqqdysdfqilpy---n--egdsa-lsl-qdrsesild-amentioning
confidence: 99%
“…It has been suggested that the conserved portion of the ectodomain may be involved in ligand interactions with a cellular receptor for the G protein (Johnson et al, 1987;Collins, 1991Collins, , 1996. However, the disulfide linkage pattern of this region of the isolated protein remains to be elucidated.…”
Section: Ssqksn-seiqqdysdfqilpy---n--egdsa-lsl-qdrsesild-amentioning
confidence: 99%
See 1 more Smart Citation
“…The attachment (G) glycoprotein is one of the major transmembrane glycoproteins and, together with the F protein, an important antigen that stimulates the protective immune response [Sullender, 2000;Cane, 2001]. The G protein coding gene is one of the most genetically variable regions of the genome [Johnson et al, 1987;Sullender, 2000;Cane, 2001]. The G gene consists of two variable parts, the N-terminal and the C-terminal, and a central, conserved region [Johnson et al, 1987;Cane et al, 1991;Sullender et al, 1991;Sullender, 2000;Cane, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…Within the mucin-like ectodomain of BRSV G exists a region spanning amino acids 166-186, that was fully-conserved among nine BRSV isolates studied [6]. This conserved region contains four cysteine residues, which are disulfide-linked, forming a characteristic "cysteine noose" that may serve to stabilize the area and be critical for receptor binding [7]. Bastien et al , identified a synthetic peptide corresponding to this conserved region that was able to induce significant BRSV-specific antibodies in calves and was capable of preventing BRSV-associated pneumonia in the natural host [8].…”
Section: Introductionmentioning
confidence: 99%